Antibody to phosphatidylethanolamine in a patient with lupus anticoagulant and thrombosis. Issue 2 (February 1989) - Staub, H L; Harris, E N; Khamashta, M A; Savidge, G; Chahade, W H; Hughes, G R
Abstract : Most patients with lupus anticoagulant (LA) activity have coincident antibodies to a group of negatively charged phospholipids, and its is suggested that LA and anticardiolipin tests detect antibodies with overlapping specificities. Some discordance between the two assays has been described, however. One patient presenting with severe thrombotic disease (recurrent deep vein thrombosis, pulmonary embolism, inferior venocaval obstruction, myocardial infarction, and digital gangrene) showed strong LA activity in February 1987. An enzyme linked immunosorbent assay (ELISA) showed no binding to the negatively charged phospholipids cardiolipin, phosphatidylserine, and phosphatidic acid, but binding to zwitterionic phosphatidylethanolamine (PE) was demonstrated. Inhibition studies and affinity purification confirmed this finding. Interestingly, the serum did not bind to the kaolin cephalin clotting time reagent when used as antigen in an ELISA. The pathogenic significance of anti-PE antibodies and their relation to LA remains to be clarified. Further studies of the occurrence of anti-PE antibodies in patients with LA activity who have negative anticardiolipin tests are suggested.